Hubungan Dukungan Suami Dengan Keikutsertaan Kb Jangka Panjang Di BPM Retno Edi S,Amd.Keb Sidoarjo - Fauziah Fitri Hernanto (NERSMID : Jurnal Keperawatan dan Kebidanan, 2018)
ABSTRACT One the factors that influence the succes of family planning is husband support. Based on BKKBN data until the end of December 2015, the quantity of PUS (Couple Age Fertile) amounted to 13,46%. This figur is lower than the achievement in 2014 which amounted to 16,51%. While for acceptor of KB injection equal to 49,93%, pill 26,36%, IUD 6,81%, implant equal to 9,63%, other method 2,1% (BKKBN, 2016). This study aims to determine the relationship of husband support with long-term family participation in BPM Sri Hastuti S.ST Surabaya. The type of this research is the observasional design of the population in this study is the family planning acceptors which amounted to 45 people, the sample in this study is the family planning acceptors in July 2017 which amounted to 40 people. The data of this research was done in July 2017 by using questionnaire and presented in diagram. Family planning acceptors who have husband support in the selection of long-term contraceptives is 5 people (12%) who didn’t participate some 35 people (88%). The quantity of family planning acceptors taking long-term contraceptive methods was 19 (47%) while those who did not participated in 21 people (53%). Based on statistical test using chi square, it is found that p value 0,012 < α (0,05) and calculate value x² 6,316 > count value 3,841, in other words, Ho is rejected and Hi is accepted so it can be concluded that there is relationship of husband support with long-term family participation. This is in accordance with the theory that a wife in decision making to use contraception requires approval from the husband because the husband is seen as the head of the family.